Preliminary re-adjusting local ecotourists' perception on outdoor recreation service quality instrumentation / Mohd Noorazlan Ab Aziz ... [et al.] - Ab Aziz, Mohd Noorazlan; Samat, Hajar Asmidar; Che Mat, Hisyam; Hashim, Mustakim; Basal, Helme; Shafiee, Mohd Shariman; Muhammad Rafiai, Nurul Ain (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study aimed was to re - adjusting the validity and reliability dimensions of ECOSERV towards outdoor recreation service quality especially at Sungai Itek, Gopeng, Perak, Malaysia. ECOSERV instrument was developed by Khan in 2003 and it was used to measure ecotourists' expectation and perceptions on service quality of localization. This instrument consists of 30 items and grouped into six (6) service dimensions. All the six (6) dimensions are Ecotangible, Assurance, Reliability, Responsiveness, Empathy, and Tangible. Each dimension had a different aspect of criteria that has been measured. Ecotangibles referring to physical facilities and equipment that were safe and appropriate to the environment. Hundred (n = 100) of respondents were involved in this study. Content validity and face validity were employed to measure the appropriateness and meaningfulness of each item in every dimension regarding the contents and constructs. Hence, Cronbach's alpha coefficient values used to determine the internal consistency. Based on findings, Cronbach's alpha coefficient values was questionable where there are three items out of 30 items in the 3 dimensions were obtained an alpha value < .7. The items and dimensions as followed; "materials reflect local influence" which in the dimension of Tangible, "provide local entertainment" which in the Assurance, and "facilities reflect local influence" in the dimension of Empathy were α =.66, α =.57 and α = .67. Therefore, the study advised to delete one or two items in each of these 3 dimensions to ensure the higher reliability of each dimension concerned in actual measuring construct. Hence, as these 3 items from suggested in each dimension were deleted, the alpha values showed higher internal consistency for Tangible, Assurance and Empathy dimension. Results of alpha values for the both perception of expectation scores α=.89, α=.80, α=.83 and perception of performance, α=.93, α=.94, α=.93. These indicated that each item that was fit by this re-justifying ECOSERV of this study and available to be used locally or abroad.